MASALAH-MASALAH REMAJA YANG MEMILIKI ORANG TUA TUNGGAL DI JORONG TARATAK TANGAH KABUPATEN SOLOK - Farida, Lasma; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
This Problems based on the phenomenon that researchers found in the field that some teens who have single parents tended to have problems such as pessimistic, role in the adjustment disorder, easily discouraged, tend to be mischievous, shy and low self-esteem. So,the researchers raised concerns about: How the problems of teenagers who have a single parent views of internal and external factors. Aim of this research was: describe the problems teenagers who have single parents views of internal and external factors in Taratak Tangah. This research was a descriptive research and the population is totaling 20 people. This research took a sample of the whole members as research subjects. Sources of data in this research are primary data and secondary data. The collection of the data through questionnaires and data was analyzed by percentage analysis. Based on the results above it can be concluded that the problems of adolescents who have single parents in Taratak Tangah Solok, from internal factors that include: 1) anxiety belong to much category, 2) depression classified as category much, 3) less have social responsibility was much, 4) have a low self worth self- classified as category a lot. Seen from external factors that include 1) racing on the streets belong to the category of a lot, 2) delinquent behavior classified as a lot categories, 3) crime and other violations belong to lot categories) addiction and drug addiction classified as a lot categories.